THE IMPORTANCE OF CHILDREN CORRECTIONAL INSTITUTION PROGRAM EVALUATION: AN EFFORT TO FULFILL CHILDREN'S RIGHTS - Adlia Rahma Maulida; Hadiyanto Abdul Rachim; Eva Nuriyah Hidayat (Social Welfare Study Program, 2023)
Abstract. The process of evaluating the quality of a program is essential in a service organization. This research aims to evaluate the service program process for correctional students at LPKA Class II Jakarta. This research is based on the evaluation concept according to Pietrzak et al which consists of four dimensions of service process evaluation: best practice standards, agency policies, process goals, and client satisfaction. This research method uses a qualitative approach using non-participatory observation techniques, in-depth interviews and a literature study. The research results show that the quality of the Development Program services at LPKA Class II Jakarta in the best practice standard dimension is under the SOP, institutional policies are running according to provisions, and long-term and short-term process goals have been implemented. In client satisfaction, service quality has been met, and LPKA Class II Jakarta has implemented a sound education service management system by implementing fair and non-discriminatory coaching. It can be concluded that the ongoing coaching program has been run by applicable provisions and standards with the implementation of process objectives and the fulfilment of inclusive education services. In the absence of social workers in the correctional sector at LPKA Class II Jakarta, some roles are not being carried out. This research further recommends the application of social welfare science and the part of correctional social workers in the practice of developing students in correctional institutions.Keywords: Program evaluation; correctional; children against the law Abstrak. Proses evaluasi kualitas suatu program sangat penting dalam suatu organisai pelayanan. Penelitian ini bertujuan mengevaluasi proses program layanan kepada correctional students pemasyarakatan di LPKA Kelas II Jakarta. Kajian ini didasarkan atas konsep evaluasi menurut Pietrzak, dkk yang terdiri dari empat dimensi evaluasi proses pelayanan; standar praktik terbaik, kebijakan lembaga, tujuan proses, dan kepuasan klien. Metode penelitian ini menggunakan pendekatan kualitatif dengan menggunakan teknik observasi non partisipatif, wawancara mendalam dan studi literatur. Hasil penelitian menunjukkan bahwa kualitas layanan Program Pembinaan di LPKA Kelas II Jakarta dalam dimensi standar praktik terbaik berjalan sesuai SOP, kebijakan lembaga berjalan sesuai ketentuan, pada tujuan proses jangka panjang dan jangka pendek sudah terlaksana. Dalam dimensi kepuasan klien kualitas layanan sudah terpenuhi dan pihak LPKA Kelas II Jakarta sudah menerapkan sistem manajemen pelayanan pendidikan yang baik dengan memberlakukan pembinaan yang adil dan tidak membeda-bedakan. Dapat disimpulkan bahwa program pembinaan yang berlangsung sudah berjalan sesuai ketentuan dan standar yang berlaku dengan terlaksananya tujuan proses serta terpenuhinya pelayanan pendidikan yang inklusif. Dengan tidak adanya pekerja sosial di bidang koreksional pada LPKA Kelas II Jakarta, ada peran-peran yang tidak terlaksana. Penelitian ini selanjutnya merekomendasikan penerapan ilmu kesejahteraan sosial dan peran pekerja sosial koreksional dalam praktik pembinaan terhadap correctional students di lembaga pemasyarakatan. Kata Kunci: Evaluasi program, Pembinaan, Anak berhadapan dengan hukum